The contribution of teachers to developing principle of submission to Allah, at secondary school students in Jeddah - Yahya, Hasan Ibrahim Ahmed (Journal of Educational and Psychological Sciences, 2019)
This study aimed to identify the degree of contribution of teachers to develop principle of submission to God, at secondary school students in Jeddah, from the perspective of students and high school students, in addition to the disclosure of the significance of the statistical differences in the assessment of students and high school students to the extent the contribution of teachers in the development of the principle of submission to God, which is attributable to sex and section in which the student studies.Use descriptive analytical method, where consisted of (34) items distributed on four axesThe study population consisted of (433) questionnaire (183) of the students and (250) of the students.Results of the study: The study reached the following conclusions:- That the overall average ratings of degrees contribution of teachers in the development of the principle of submission to God, to the students of secondary schools in Jeddah was (3.48) medium degree of contribution. The field was to contribute to the delivery Elimination much the first level and then moderately delivery texts legitimacy second level and then moderately delivery matters metaphysical level third moderately contribution limits and then delivery promises moderately and the last level.- A statistical differences at the level of significance (0.05 = α) in estimating the degree of contribution of teachers in the development of the principle of submission to God, and areas due to sex in favor of females.- There are statistical differences at the level of significance (0.05 = α) in estimating the degree of contribution of teachers in the development of the principle of submission to God, attributed to the department in favor students of the scientific section degree total the areas of religious texts, borders and promises.- There are statistical differences at the level of significance (0.05 = α) in estimating the degree of contribution of teachers in the development of the principle of submission to God, degree college attributed to the interaction of the two variables of sex and Section female literary in favor and scientific females, and the field of religious texts in favor scientific males then literary females in the field of fate and destiny female literary in favor while it did not identify differences in the field of border and promisesMust work on training teachers to link educational content to the principle of submission to God, and to emphasize the importance of the role of teachers in submission to God, through the development of the educational role that they are the methods.
Keywords: submission to God Almighty; legal texts; unseen matters; limits; promises and threats; predestination and predestination; teachers' contribution